Donor hypernatremia is associated with increased mortality after heart transplantation. (3rd October 2022) - Oehler, D; Immohr, M; Boettger, C; Erbel-Khurtsidze, S; Aubin, H; Bruno, R; Holst, T; Horn, P; Westenfeld, R; Kelm, M; Tudorache, I; Akhyari, P; et al.
Abstract: Objective: Donor hypernatremia has been associated with primary graft dysfunction in heart transplantation and is known to be associated with impaired outcome following liver and renal transplantation. However, controversial data exist regarding the impact of sodium deregulation in patient survival after heart transplantation (HTx). This study aims to investigate the impact of donor sodium levels on early morbidity and short- and midterm survival following HTx. Methods: Between September 2010 and June 2021, a total of n=218 patients underwent HTx in our centre. From those, 214 could be included retrospectively in our study. For each donor, sodium levels were collected and different cut-off levels from 145 to 159 mmol/l were investigated by Kaplan-Meier-analysis. Then, recipients were divided in three groups regarding donor sodium: Normonatremia (133–145 mmol/l, n=73), mild hypernatremia (146–156 mmol/l, n=105) and severe hypernatremia (>156 mmol/l, n=35). Recipient and donor variables were reviewed and compared, including peri- and postoperative characteristics and recipient survival after up to 5 years after transplantation. Results: All patients were comparable regarding baseline characteristics and perioperative parameters. Regarding early mortality, 90-day survival was significantly reduced only in patients with severe donor hypernatremia in comparison to normonatremia (see table 1 and fifgure 1, 90% vs. 71%, p=0.02), but not in mild normonatremia (89%, p=0.89). 1-year survival was comparable in all groups (p>0.28). Conclusion: Donor hypernatremia was associated with reduced short-term survival, while correlation weakens >1 year after HTx. Future prospective studies are needed to confirm the possible cut-off value of 156 mmol/l for donor-acceptancy. Funding Acknowledgement: Type of funding sources: None.